Sintesis Dimerkaptoetil Adipat sebagai Bahan Baku Stabiliser Termal Polivinil Klorida berbasis Timah Organik Ester Balik - Putrawan, I Dewa Gede Arsa; Natan, Nikanor; Syakuron, Rizal Abdan (Indonesian Journal of Chemical Research, 2020)
This research aimed to study the synthesis of dimercaptoethyl adipate as raw materials for polyvinyl chloride thermal stabilizer from mercaptoethanol and adipic acid in a batch reactor in which water as a side product was removed by azeotropic evaporation. The study was done through comparative experimental tests where the factors studied included entrainer, mercaptoethanol excess, and reactor volume. It was found that the products obtained were liquid at room condition having clarity in the 95%-99% range, sulfhydryl content in the 23.3%-24.3% range, and yield in the 83.7%-92.1% range. Clarities, sulfhydryl contents, and yields at 20% and 40% mercaptoethanol excesses were not significantly different. At 1 L and 5 L reactor volumes, sulfhydryl contents were found to be significantly different but clarities and yields were not significantly different. Both n-hexane and cyclohexane could be used as entrainers to remove water in the synthesis of dimercaptoethyl adipate. Both entrainers gave clarities and yields that are not significantly different. n-hexane resulted in sulfhydryl content which was 0.77% higher than that of cyclohexane. However, bearing in mind health factors, cyclohexane is considered to be better than n-hexane.